Evaluation of the hygienic-sanitary conditions of butcher in open market in the Municipality of Mamanguape, Paraiba State, Brazil (Research, Society and Development, 2020)
Free trade fairs are considered places favorable for the dissemination of food diseases, through the intense circulation of products and people, in the same environment, together with undesirable hygiene and sanitary conditions. The research aims to analyze the hygienic-sanitary conditions of butcher in open fair in the municipality of Mamanguape-PB. For this, a study was developed based on field visits to ten butchers in the municipality, six of these, accepted to participate in the present study, being coded as: A1, A2, A3, A4, A5 and A6. In order to evaluate the good practices of manipulation, a checklist was used based on RDC Ordinances No. 275 of October 21, 2002 and RDC No. 216 of September of 2004. The results showed that the majority of the evaluated establishments presented higher percentages refrigeration / freezer / refrigerated counter, exhibition area for sale, waste, integrated pest control, installations / buildings and documentations. In this way, evidence the need for awareness-raising work, through public agencies, through courses related to the manual of good practices, since this tool is indispensable in the processing and marketing of food.